Low-Cost Extra-Low Voltage LED Dimmer for Tuneable White Lighting - Hrbac, Roman; Mlcak, Tomas; Kolar, Vaclav; Vantuch, Tomas (Elektronika ir Elektrotechnika, 2019)
The colour appearance of light sources has a major impact on how people perceive space. With LED illumination lighting, the colour output can be tuned to virtually any perceivable colour, including any hue of white light. It has been established that the right shade of white light during the 24-hour day cycle has a positive effect on the human body’s biological system. For this reason, it is very important to focus on the development and application of new lighting systems that have dynamically variable light outputs in order to imitate the sunlight. Circadian regulation is most responsive to short-wavelength light (460 nm = blue colour). This paper describes the development of a low-cost extra-low voltage LED dimmer for tunable white lighting systems aiming to achieve maximum electrical performance and light-output. This dimming module has two independent LED control channels and allows for a variable colour temperature control from warm white to cold white light. Experimental results of the dimming module efficiency measurements, correlated colour temperature (CCT), colour rendering index (CRI), illuminance and power consumption of the luminaire depending on the duty cycle for different control frequencies (200 Hz, 1.5 kHz, 5 kHz, 10 kHz and 20 kHz) are presented. The paper further describes the principle of creating control curves for an independent regulation of correlated colour temperature and illuminance. In the form of a table, the control curve outputs may be uploaded into a microcontroller. The paper details the construction, function and the advantages of this LED dimmer prototype.